Channel characterization of non-line of sight propagation - Tan, Henry Philip. (2011)
Ships are constructed using metals which are good reflectors of electromagnetic (EM) waves [1]. Therefore, signal propagation in a sea environment is more complex as compared to propagation indoor. This complexity would allow us to study the feasibility of applying narrowband or/and broadband signals for wireless communication on board a boat (transmitter) to the shore (receiver) while being blocked by a vessel in the sea (NLOS).